Influence of land use on the trophic niche overlap of dung beetles in the semideciduous Atlantic forest of Argentina - Giménez Gómez, Victoria Carolina (2018)
Fil: Giménez Gómez, Victoria Carolina. Universidad Nacional de Misiones. Instituto de Biología Subtropical. Nodo Puerto Iguazú; Argentina.